First-trimester maternal concentrations of polyfluoroalkyl substances and fetal growth throughout pregnancy. (September 2019) - Costa, Olga; Iñiguez, Carmen; Manzano-Salgado, Cyntia B.; Amiano, Pilar; Murcia, Mario; Casas, Maribel; Irizar, Amaia; Basterrechea, Mikel; Beneito, Andrea; Schettgen, Thomas; Sunyer, Jordi; Vrijheid, Martine; et al.
Abstract: Background: Several studies have investigated the possible association between prenatal exposure to perfluoroalkyl substances (PFASs) and birth anthropometry. However, none has assessed fetal size longitudinally. We studied the possible association between PFASs and fetal biometry. Methods: In 1230 mother–child pairs of three cohorts from the Spanish INMA-Project, we analyzed perfluorohexanesulfonic acid (PFHxS), perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA) in first-trimester maternal plasma (collection: 2003–2008). We measured abdominal circumference (AC), femur length (FL), biparietal diameter (BPD), and estimated fetal weight (EFW) by ultrasounds at 12, 20, and 34 gestational weeks. We conducted multivariable linear regression analyses between log2 -transformed (PFASs) and SD-scores of fetal parameters in each cohort and subsequent meta-analysis. We also assessed effect modification by sex and maternal smoking. Results: PFHxS, PFOA, PFOS, and PFNA medians were: 0.58, 2.35, 6.05, and 0.65 ng/mL, respectively. There were no associations for the whole population in any trimester of pregnancy. However, we found an indication that maternal smoking modified the effect in different directions depending on the PFAS. Among smokers (31%), we found negative associations between both PFOA and PFNA and FL or EFW at week 20 (% change ranging between −6.8% and −5.7% per twofold PFAS increase) and positive associations between PFHxS or PFOS and BPD at week 34 (6.8% and 6.3%, respectively). Conclusions: Results did not suggest an overall association between prenatal PFASs and fetal growth. The results among smokers should be taken with caution and further studies are warranted to elucidate the possible role of smoking in this association. Highlights: First study on maternal PFASs and fetal growth assessed longitudinally by ultrasounds No evidence of an association between prenatal PFAS exposure and fetal growth However, there was effect modification by maternal smoking during pregnancy. Associations were only found among smokers with different directions depending on the PFAS.